Literasi Informasi Siswa Kelas X Jurusan Administrasi Perkantoran di SMK Nusatama Padang - Nia, Intan; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractIn this paper, a review of information literacy is discussed for class X Office Administration Department at Nusatama Padang Vocational School. This study aims to find out how information literacy in class X Office Administration Department at Nusatama Vocational School Padang. This study uses a descriptive method with a quantitative approach, which is collecting data directly by distributing questionnaires to class X students of the Office Administration Department at Nusatama Vocational School Padang. Based on the analysis of the data it can be concluded that the information literacy skills of class X Office Administration Department at Nusatama Padang Vocational School are still not good, because in information literacy activities in class X Office Administration Department of Nusatama Padang Vocational School often misuse media use in seeking information carried out by students. Students use smartphones in search of information, but there are still many class X students who use smartphones as a medium for entertainment. Student knowledge about information literacy activities is still not good. Many students still do not understand the ethics and stages of finding good and true information. This results in frequent occurrence of students who are wrong in getting and using information. In addition, in the evaluation activities there are not many students who rank the level of usefulness of the information they need, students only search for information and get it without reading and understanding the information to be used in advance. So, from the results obtained it can be said that students of Class X Office Administration Department at Padang Nusatama Vocational School still lack understanding of actual information literacy skills and Class X students of Office Administration Department are still classified as students who fail information literacy.Keywords: information, literacy.